Studies on the sintering of silicon dioxide - Singh V.K. (My University, 2025)
Sintering studies were carried out on SiO2 by taking compacts of different particle sizes of double calcined silicon dioxide. Effects of particle size, sintering temperature and sintering time were investigated. The data were analysed using the empirical equation D = K log t + C. It was observed that the activation energy for sintering of SiO2 increases with increase in particle size from -45 µ to-106+90 µ powder. © 1977, Taylor & Francis Group, LLC.